Dynamic model for risk analysis of picture archiving communication system (PACS) at Hospital Selayang - Omar, Nazrool (2008)
Risk analysis is the best method for every organization to secure their business environment from any undesired hazardous events such as malicious code attack or natural disaster that could cause a lot of loses and impairs business operation. Risk analysis is very important and necessary because the probability of a disaster occurring in an organization is highly uncertain. Hence, the prediction through analysis process is mandatory. Selecting methodology for information security risk analysis is crucial. This project analysis will follow ISO/IEC 27005 Information Security Risk Management Standard. This standard has been widely used as baseline or references by many commercial risk analysis tool developers. The risk analysis is carried out on Pictures Archiving and Communication System (PACS) of Hospital Selayang. The analysis attempts to identify and list the risks that might shut down the system operation and subsequently presented in Dynamic Fault Tree (DFT) as a dynamic model. Dynamic Fault Tree is a method that extends standard fault trees by allowing the modeling of system risks behaviors and interactions with each other over a period of time. At the end of the project risks register will be produced in the form of report. The risk report will benefit Hospital Selayang during overall risk assessment of the Pictures Archiving and Communication System (PACS).